The relationship between ventricular size and visual function in children with hydrocephalus (1998)
We examined the relationship between ventricular size and visual function in 50 children (36 males and 14 females) with hydrocephalus. The third and lateral ventricular sizes and the visual function scores did not significantly differ between the sexes. Ventricular enlargement was most pronounced at the trigones and least at the level of the foraminae of Monro. The visual function score correlated inversely with the size of the lateral ventricle measured at the levels of the anterior horn and the trigone and expressed as coronal diameter and "Modified" Evans' ratio (r = 0.49; P = 0.001 and r = - 0.38, P = 0.01 for the anterior horn; r = 0.48, P = 0.00 I and r = -0.35, P = 0.001 for the trigone). The size of the third ventricle did not correlate with visual function score. A "modified" anterior Evans ratio of 0.60 and a trigonal Evans ratio of 0.73 were associated with very low visual function score. Furthermore, there was significant inverse correlation between occipitofrontal circumference (OFC) and visual function (r = -0.6379, P = 0.001), but OFC was not valuable for predicting visual function before the onset of head enlargement.